Suppression of enteroendocrine cell glucagon-like peptide (GLP)-1 release by fat-induced small intestinal ketogenesis: a mechanism targeted by Roux-en-Y gastric bypass surgery but not by preoperative very-low-calorie diet. Issue 8 (21st November 2019) - Wallenius, Ville; Elias, Erik; Elebring, Erik; Haisma, Bauke; Casselbrant, Anna; Larraufie, Pierre; Spak, Emma; Reimann, Frank; le Roux, Carel W; Docherty, Neil G; Gribble, Fiona M; Fändriks, Lars
Abstract : Objective: Food intake normally stimulates release of satiety and insulin-stimulating intestinal hormones, such as glucagon-like peptide (GLP)-1. This response is blunted in obese insulin resistant subjects, but is rapidly restored following Roux-en-Y gastric bypass (RYGB) surgery. We hypothesised this to be a result of the metabolic changes taking place in the small intestinal mucosa following the anatomical rearrangement after RYGB surgery, and aimed at identifying such mechanisms. Design: Jejunal mucosa biopsies from patients undergoing RYGB surgery were retrieved before and after very-low calorie diet, at time of surgery and 6 months postoperatively. Samples were analysed by global protein expression analysis and Western blotting. Biological functionality of these findings was explored in mice and enteroendocrine cells (EECs) primary mouse jejunal cell cultures. Results: The most prominent change found after RYGB was decreased jejunal expression of the rate-limiting ketogenic enzyme mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase (mHMGCS), corroborated by decreased ketone body levels. In mice, prolonged high-fat feeding induced the expression of mHMGCS and functional ketogenesis in jejunum. The effect of ketone bodies on gut peptide secretion in EECs showed a ∼40% inhibition of GLP-1 release compared with baseline. Conclusion: Intestinal ketogenesis is induced by high-fat diet and inhibited by RYGB surgery. In cell culture, ketone bodies inhibited GLP-1 release from EECs. Thus, we suggest that this may be a mechanism by which RYGB can remove the inhibitory effect of ketone bodies on EECs, thereby restituting the responsiveness of EECs resulting in increased meal-stimulated levels of GLP-1 after surgery.